Cultural capitals revaluing the arts, remaking urban spaces - Johnson, Louise C. 1953- (Ashgate, 2009)
"This is a book about the power of the arts to enhance city images, urban economies and communities. Anchored in academic discussion of the Cultural Industries - what they are, how they have emerged, why they matter and how they should be theorized - the book offers a series of case studies drawn from five countries: Australia, Singapore, Spain, the UK and the US to examine how the arts contribute to sustainable urban regeneration." -- Book cover.
Includes bibliographical references and index
Keywords: Urban renewal; Arts and society; Stadtumbau; Dienstleistungssektor; Wirtschaftsentwicklung; Kulturelle Entwicklung; Fallstudiensammlung